Pengaruh Terapi Akupresur dan Water Sound Terhadap Penurunan Kecemasan Ibu Hamil dengan Prematur Kontraksi di RSUD Kembangan: Pengaruh Terapi Akupresur dan Water Sound Terhadap Penurunan Kecemasan Ibu Hamil dengan Prematur Kontraksi - Koriyanah; Purnama , Agus; Susaldi (STIKES Ngesti Waluyo, 2024)
Pregnant women are the occurrence of premature contractions that cause anxiety when premature contractions occur. Pharmacological and non-pharmacological therapies can be used to overcome anxiety for pregnant women. Non-pharmacological therapies are alternative options such as relaxation, acupressure, massage, acupuncture, warm compresses, music, and aroma therapy. The purpose of this study was to identify the effect of acupressure and water sound therapy on reducing the anxiety of pregnant women with premature contractions at Kembangan Hospital. The design or type of research used in this study is Quasi-experimental research. Population is the whole object of research or the object under study. The population in this study were pregnant women with premature contractions of 20-37 weeks of gestation at Kembangan Hospital. The sample involved in this study, based on the results of the above calculations, consisted of 13 respondents per group. The sampling technique used was purposive sampling. Purposive sampling. In this study, the research instrument or tool used to collect data is the HARS (Hamilton Anxiety Rating Scale) Questionnaire sheet. Data analysis using paired t-test. The results of acupressure therapy research had a p-value of 0.000. Water sound therapy with a p-value of 0.000. Combination therapy of acupressure and water sound with a p-value of 0.000. Conclusion There is an effect of acupressure therapy, water sound, and a combination therapy of acupressure therapy and water sound on reducing the anxiety of pregnant women with premature contractions at Kembangan Hospital. Recommendations for services at Kembangan Hospital are that acupressure therapy, water sound, and a combination of both be applied in an effort to reduce the anxiety of pregnant women with premature contractions.